Evaluating the independent influence of sexual transmission on HBV infection in China: a modeling study - Miaolei Li; Jian Zu; Mingwang Shen; Guihua Zhuang; Siyuan Chen; Fuzhen Wang; Hui Zheng; Guomin Zhang (BMC, 2021)
Abstract Background The long-term impact of sexual transmission on the hepatitis B virus (HBV) infection in China remains unclear. This study aims to estimate the independent influence of sexual transmission on HBV infection. Methods Based on the natural history of HBV infection and three national serosurvey data of hepatitis B in China, we developed an age- and sex-specific discrete model to describe the transmission dynamics of HBV. The initial conditions of the model were determined according to the age- and sex-specific national serosurvey data in 1992. Based on the national survey data of hepatitis B in 1992 and 2006, by using the Markov Chain Monte Carlo (MCMC) method, we estimated the age- and sex-specific seroclearance rates of hepatitis B surface antigen (HBsAg) and the horizontal transmission rates as well as their 95% confidence intervals (CI). Then we used the age- and sex-specific national serosurvey data of hepatitis B in 2014 to test the accuracy of our model-based estimation. Finally, we evaluated the independent impact of sexual transmission on HBV infection and discussed the long-term effect of promotion of condom use in China. Results We estimated that the annual rates of HBsAg seroclearance for males and females aged 1-59 years were respectively 1.04% (95% CI, 0.49-1.59%) and 1.92% (95% CI, 1.11-2.73%). Due to sexual transmission, in 2014, the total number of chronic HBV infections in people aged 0-100 years increased 292,581, of which males increased 189,200 and females increased 103,381. In 2006, the acute HBV infections due to sexual transmission accounted for 24.76% (male: 31.33%, female: 17.94%) and in 2014, which accounted for 34.59% (male: 42.93%, female: 25.73%). However, if the condom usage rate was increased by 10% annually starting in 2019, then compared with current practice, the total number of acute HBV infections from 2019 to 2035 would be reduced by 16.68% (male: 21.49%, female: 11.93%). The HBsAg prevalence in people aged 1-59 years in 2035 would be reduced to 2.01% (male: 2.40%, female: 1.58%). Conclusions Sexual transmission has become the predominant route of acute HBV infection in China, especially for men. The promotion of condom use plays a significant role in reducing the cases of acute HBV infection.